The Relationship Between Religion and Politics of Muhammad Iqbal: A Philosopical and its Relevance - Ghaffari , Fathul; Faizin , Khoirul; Afif , Ahmad; Karimullah , Suud Sarim; Fathony , Moh. Rosil (Suhuf: International Journal of Islamic Studies, 2025)
From classical times to the modern era, the relationship between religion and politics has been a never-ending debate. On the one hand, religion is considered a moral foundation that directs political action towards justice and the welfare of the people, while on the other hand, the political world is often separated from the spiritual dimension to maintain objectivity and individual freedom. In this article, Muhammad Iqbal, a prominent Muslim thinker from the 20th century, opposes secularism and proposes a spiritual democracy system, which combines the principles of democracy with Islamic values to create a just and prosperous government. Through ijtihad, Muslims are invited to interpret Islamic teachings to be relevant to the challenges of the times. The research method uses qualitative with a literature study approach (library research). The main focus of this study is how Muhammad Iqbal views the relationship between religion and politics, and to what extent Muhammad Iqbal's thoughts are relevant in the modern era. The results of this study found two interesting things, namely: first, Muhammad Iqbal's thoughts on the relationship between religion and politics emphasize the importance of combining the principles of democracy and Islamic moral values in the system of government. Second, Muhammad Iqbal's thoughts on the relationship between religion and politics remain relevant in the modern socio-political context.